NILAI-NILAI DEMOKRASI SEBAGAI PENGUATAN PENDIDIKAN ISLAM DI MAN 1 PANDEGLANG - Muhamad Sudi, Didih; Kurnaesih, Uun; Maryam, Siti; Supardi, Supardi (Staisman Press, 2022)
This study aims to find out instilling democratic values ​​in Islamic education, there is a strategy carried out by MAN 2 Pandeglang through teaching and learning activities and also holding routine activities related to democratic behavior, both in theory in the teaching and learning process, as well as in practice in teaching and learning. student daily life. The method used in this research is descriptive qualitative analytical method using data collection techniques in the form of observation, interviews and documentation studies. This research proves that education held at MAN 2 Pandeglang. The results showed that education that contains democratic values ​​based on an integral education system based on monotheism, namely education that integrates formal education with boarding education, among democratic values ​​that run in the implementation of education at MAN 2 Pandeglang with various characters and personalities, students are always taught and accustomed to tolerance, mutual respect, and mutual respect for differences so that students are given the freedom to be creative and express their interests and talents in accordance with the potential of each student